A City between the Global and the National: U.S. Navy's Peacemaking Mission in Split, 1918-1921 - Perica, Vjekoslav (Array, 2008)
Article uses US naval archives to analyze one of earliest successful peacekeeping operations in history. One of reasons for success was US navy's management of a complex situation but also interaction with the local community.